Homogeneity or Heterogeneity of Groups: When, and Along What Dimensions? - Adler, Michael (Canadian Journal of Counselling and Psychotherapy, 2007)
Low awareness of the interplay of homogeneity-heterogeneity variables in group composition may limit the counsellor's choices from the therapeutic menu. Multi-dimensional homogeneity is generally accepted for support or one issue oriented groups. However, for more ambitious change-oriented groups compositional considerations become more complex. Fc these groups, the paper suggests homogeneity in clients' tolerance of anxiety, motivatior mental and social abilities, and exclusion criteria, whereas it argues for a heterogeneity alon almost all other dimensions. Understanding the interplay of these variables may substantiall broaden the group counsellor's repertoire of therapeutic approaches.